Effect of Some Organic Matter Sources on Nutrient Availability, Humus Buildup, Soil Physical Properties and Wheat Yield Under Field Conditions - Somani, L L; Saxena, S N (Annals of Arid Zone, 2016)
A field trial involving three levels of some organic matter sources representing wide and Darrow C:N, C:P and C:S ratio was carried out using wheat (Kalyan Sona) as the test crop. Wide ratio materials like wheat straw and rice husk although markedly improved soil physical properties including structural index and also K supply potential, but affected the yield adversely due to immobilization of nitrogen, phosphorus and sulphur. Application of narrow ratio materials like FYM and poultry manure increased the availability of nitrogen, phosphorus and sulphur and consequently increased the crop yield more so with the higher, levels used. FYM and poultry manure were found to be good sources from organic matter buildup in the soil. All these sources significantly, increased humic acid content and decreased fulvic acid contents over control. The humic acid C/fulvic acid C ratio was considerably higher under treatments involving additions of wheat straw and rice husk.